2019
DOI: 10.1360/ssv-2019-0089
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of mitochondrial deoxyguanosine kinase in lung cancer tumorigenesis

Abstract: Articles you may be interested in BCI induces apoptosis via generation of reactive oxygen species and activation of intrinsic mitochondrial pathway in H1299 lung cancer cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…In our previous studies, we found that DGUOK deletion affected the assembly of mitochondrial complex I, and robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self-renewal(33, 34). We also found DGUOK regulates nicotinamide adenine dinucleotide (NAD + ) biosynthesis independent of the mitochondrial complex I (35).…”
Section: Resultsmentioning
confidence: 94%
“…In our previous studies, we found that DGUOK deletion affected the assembly of mitochondrial complex I, and robustly inhibited lung adenocarcinoma tumor growth, metastasis, and CSC self-renewal(33, 34). We also found DGUOK regulates nicotinamide adenine dinucleotide (NAD + ) biosynthesis independent of the mitochondrial complex I (35).…”
Section: Resultsmentioning
confidence: 94%
“…In our previous studies, we found that DGUOK deletion affected the assembly of mitochondrial complex I and robustly inhibited lung adenocarcinoma tumor growth and metastasis and CSC self-renewal [ 34 , 35 ]. We also found that DGUOK regulated nicotinamide adenine dinucleotide (NAD + ) biosynthesis independent of mitochondrial complex I [36] .…”
Section: Resultsmentioning
confidence: 99%
“…Figura 4.7: A: Western blot mostró que dguok estaba completamente eliminado en H1650;D: Western blot mostró que dguok fue eliminado por completo en A549. Imagen tomada de [29].…”
Section: La Importancia Del Gen Dguokunclassified
“…Figura 4.8: B: La eliminación de DGUOK inhibió la formación de esferas de células H1650; C: Los datos cuantifican que el knockout de DGUOK inhibe la formación de esferas celulares H1650 ; E: La desactivación de DGUOK inhibió la formación de esferas de células A549 ; F: Los datos cuantificaron que la desactivación de DGUOK inhibía la formación de esferas de células A549. Imagen tomada de [29].…”
Section: La Importancia Del Gen Dguokunclassified
See 1 more Smart Citation